(untitled) (Argos, 2025)
Among modern commentaries on Propertius, those of Fedeli on Book 1 (1980), 3 (1985) and 2 (2005) are essential for researchers on the poet of Assisi. Together with R. Dimundo and I. Ciccarelli, Fedeli is currently working on a new commentary on Book 4, of special interest because it reconsiders many textual problems and therefore offers a text quite different both of Fedeli’s early 1965 edition of Book 4 and of his critical edition of the entire corpus of 1984. The great Propertian scholar honors our review publishing some samples of this new commentary, which provide at the same time an unending lesson in philological method and expertise.